PAS jangan jadi UMNO - Dinsman, 1949- (Kuala Lumpur : Penerbitan Pemuda, 2000)
Political conditions in Malaysia; rivalry between Parti Islam Semalaysia and United Malays National Organisation.
Includes bibliographical references.
In Malay.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Parti Islam SeMalaysia; United Malays National Organisation; Islam and politics -- Malaysia; Malaysia -- Politics and government